The Comparative Treatment of Intraventricular Chemotherapy by Ommaya Reservoir vs. Lumbar Puncture in Patients With Leptomeningeal Carcinomatosis - Montes de Oca Delgado, Mariano; Cacho Díaz, Bernardo; Santos Zambrano, José; Guerrero Juárez, Vicente; López Martínez, Manuel Salvador; Castro Martínez, Elvira; Avendaño Méndez-Padilla, Javier; Mejía Pérez, Sonia; Reyes Moreno, Ignacio; Gutiérrez Aceves, Axayacatl; González Aguilar, Alberto (Frontiers in Oncology, 2018)
Object: Leptomeningeal Carcinomatosis (LCM) represents a state of systemic malignant disease with poor prognosis. The purpose of this study is to compare overall survival (OS) between intraventricular chemotherapy through Ommaya reservoir (OR) and chemotherapy through lumbar puncture (LP) in LCM. Patients & Methods: Forty adult patients with LCM were included. All patients underwent lumbar puncture and Magnetic resonance imaging (MRI). Thirty patients received chemotherapy through LP and 10 undergone colocation of Ommaya reservoir for intraventricular chemotherapy. Results: The most common symptom was headache (Present in 50%). The cranial nerves most affected were VI and VII. Leptomeningeal enhancement was the most frequent finding in MRI. The OS in the LP group was 4 months and Ommaya group was 9.2 months (p=0.0006; CI:1.8-3), with statistical differences in favor to Intraventricular treatment. Proportional hazard regression showed that receiving chemotherapy through Ommaya reservoir was a protective factor (Hazard ratio = 0.258, Standard Error = 0.112, p= 0.002 and 95% CI 0.110-0.606). Using KPS as a factor did not affect the hazard ratio of Ommaya reservoir itself. Conclusions: OS was significantly higher in patients with Ommaya reservoir in spite of Karnofsky Performance Status (KPS) previous to chemotherapy. Therefore, intraventricular chemotherapy should be preferred over lumbar puncture chemotherapy administration if there are resources available.